The Effects of Five Different Types of Acid Anhydrides and Incorporation of Montmorillonite Nanoclays on Thermosetting Resins - M. R., Islam; Beg, M. D. H.; Saidatul Shima, Jamari (Springer Berlin Heidelberg, 2015)
Five different types of acid anhydrides such as succinic anhydride (SA), maleic anhydride (MA), phthalic anhydride (PA), 3,4,5,6-tetrahydrophthalic anhydride (TPA) and cis-1,2-cyclohexanedicarboxylic anhydride (CDA) were used to prepare various polyalkyd resins from palm oil by following alcoholysis and esterification reaction. Palm oil was subjected to dehydration process using concentrated sulphuric acid prior to alcoholysis to improve the unsaturation in the fatty acid chains. Various physicochemical properties of the resins such as acid value, iodine value, yield, density, specific gravity, molecular weight, non-volatile material content, drying time, colour, solubility, etc., were tested by using standard methods. The resins were cured by using methyl ethyl ketone peroxide (MEKP), styrene and cobalt naphthenate at 120 °C. To enhance the thermal, structural and other resinous properties, 0.5 wt% of montmorillonite nanoclays (MNCs) was dispersed in TPA-based resin. The cured films were tested for X-ray diffraction, surface morphology, tensile properties, pencil hardness, gloss, gel content, swelling ratio, adhesion, thermogravimetric analysis, and chemical resistivity. In addition, hydrophobicity of the cured films was observed by contact angle measurement. A comparison was drawn among the resins as well as the films prepared from different acid anhydrides. Analysis revealed that TPA-based resin/film shows improved characteristics among the others due to high degree of crosslinking. On the other hand, incorporation of MNCs into the polyalkyds led to higher thermal properties, acceptable pencil hardness and reduced wettability, which may suit this film to be applied for high-performance surface coating applications.